PTSD, Complex PTSD, and Childhood Abuse: Gender Differences among a Homeless Sample - Sabina de Vries; Gerald A. Juhnke; Cherie Trahan Keene (Journal for Social Action in Counseling and Psychology, 2019)
The current study examined the potential relationship between homelessness, gender, and occurrence of Post-Traumatic Distress Disorder (PTSD) and Complex PTSD. Participants were 90 homeless persons from shelters located in a large, South Central Texas, metropolitan city of approximately 1.9 million persons. The study found that homeless participants reported high levels of childhood emotional, physical, and sexual abuse. Homeless women reported higher rates of childhood abuse and were affected by PTSD at a higher frequency than homeless males. PTSD, Complex PTSD, and traumatic experiences such as childhood abuse appear to be contributing factors to homelessness. Results suggest the need for increased advocacy among counseling and psychology professionals is warranted for homeless persons experiencing PTSD.